1972
DOI: 10.1021/jm00278a034
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of some spin-labeled analogs of drug molecules

Abstract: their ability to induce ataxia, to decrease locomotor activity, and to afford protection against electroshockand strychnine-induced convulsions in mice. In general, the compounds described herein failed to afford protection at an acceptable dose (<50 mg/kg) against convulsions induced by either method. However, many compounds induced ataxia, as judged by impairment of ability to traverse a suspended rod, and decreased motor activity. The data for the more interesting compounds are summarized in Table I; compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1972
1972
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…General procedure The allylic bromo compound (2 or 4) (0.50 mmol) was added to a suspension of morphine base (143 mg, 0.50 mrnol) and K2CO3 (100 mg) in DMF, and the mixture was heated (70°C) for 2 h, diluted with a solution of NH4C1, extracted with CHC13 (3 X 10 mL), dried, and evaporated. The pure product (5 or 6) was obtained by preparative Preparation of N-spin-labelled normorphine derivatives (7,8 ) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…General procedure The allylic bromo compound (2 or 4) (0.50 mmol) was added to a suspension of morphine base (143 mg, 0.50 mrnol) and K2CO3 (100 mg) in DMF, and the mixture was heated (70°C) for 2 h, diluted with a solution of NH4C1, extracted with CHC13 (3 X 10 mL), dried, and evaporated. The pure product (5 or 6) was obtained by preparative Preparation of N-spin-labelled normorphine derivatives (7,8 ) .…”
Section: Methodsmentioning
confidence: 99%
“…The 'H and 13C nmr spectra of compounds obtained from each reaction type showed that reactions with 2 and 4 had taken place without allylic rearrangement (see Table 1 and Experimental). The allyl halides (2, 4) used for alkylation of morphines have not only the advantage of higher reactivity observed in alkylation of morphine, with 2, on the phenolic hydroxyl to 5 (16), or with 4 to 6, but in alkylating the normorphine molecule with 2 or 4 the N-ally1 labelled derivatives (7,8) can be obtained. When normorphine was reacted with excess of reagents 2 and 4, the biradicals (9 and 10) were obtained.…”
Section: Oacmentioning
confidence: 99%
See 1 more Smart Citation
“…Chignell and co-workers have recently syn thesized a series of spin-labeled aromatic sulfonamides containing the nitroxide-free radical [4] and studied their interaction with bovine ery throcyte carbonic anhydrase B [3,5] and human erythrocyte carbonic anhydrase B and C [6]. In this report we show how a spin-labeled sul fonamide (I) can be used to measure the concentration of certain diuretic sulfonamides in body fluids.…”
Section: Introductionmentioning
confidence: 99%
“…For example. new spin-labeled drugs have been synthesized to study the mechanism of drug action at a molecular level and the topography of specific binding sites in receptor macro~nolecules (4)(5)(6)(7)(8).…”
mentioning
confidence: 99%